Glucose Tolerance Tests and Osteocalcin Responses in Healthy People - Starup-Linde, Jakob; Westberg-Rasmussen, Sidse; Lykkeboe, Simon; Handberg, Aase; Hartmann, Bolette; Holst, Jens J.; Hermansen, Kjeld; Vestergaard, Peter; Gregersen, Søren (Frontiers in Endocrinology, 2018)
Aims: Osteocalcin and undercarboxylated osteocalcin are suggested to be endocrine messengers from the bones and have been shown to stimulate insulin secretion from pancreatic β-cells. Insulin is hypothesized to increase the osteoblastic production of osteocalcin. The aim of the study was to investigate whether the route of glucose administration influence the circulating levels of osteocalcin and undercarboxylated osteocalcin. Methods: Twelve healthy males were enrolled in an acute cross-over study where they underwent an oral glucose tolerance test (OGTT), an isoglycemic intravenous glucose infusion (IIGI) and a fasting period (control). Blood samples were collected throughout 180 minutes and analysed for osteocalcin and undercarboxylated osteocalcin and compared to insulin, glucose, and gastro-intestinal hormone responses. Results: Neither osteocalcin levels nor undercarboxylated osteocalcin levels over time differed between the OGTT, IIGI and fasting. Baseline insulin levels and glucose levels were not associated with osteocalcin or undercarboxylated osteocalcin levels. Increases in insulin and glucose levels were neither associated with altered osteocalcin nor undercarboxylated osteocalcin levels. Conclusion: The route of glucose administration does not influence the circulating levels of osteocalcin and undercarboxylated osteocalcin despite the differential insulin and incretin responses. In the acute setting this suggests that insulin does not increase osteoblastic production of osteocalcin in healthy human males.